Multimedia-Assisted Elementary School Learning Materials Innovation Using STEAM Learning Approach - Desyandri, -; Agustina, Yana; Yeni, Indra; Parmadi, Bambang (JOIV : International Journal on Informatics Visualization, 2024)
Printed materials dominate the teaching materials used in elementary schools in Indonesia. These conditions are backward with the development of the Industrial Revolution 4.0, so it is urgent to research the effectiveness of multimedia-based teaching material using Macromedia Flash Eight application with the learning approach of Science, Technology, Engineering, Art, and Math (STEAM) in Elementary Schools. The research method used is research and development (R&D) with the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. The data collection instrument uses pre-test and post-test sheets, and an evaluation lift is open to the use of teaching materials for teachers and students. The respondents were eight teachers and 84 elementary school students. The effectiveness of the teaching material is analyzed in two ways: (1) the analysis of learning outcomes (pre-test and post-test) using the N-Gain Test, and (2) the evaluation of the product is based on the results of open-haul analysis, advice, and recommendations. This research and development results show that the pre-test average of 47,14 increased to 84.58 (post-test), while the test score of N-Gain was 71.75%, with the category quite effective. Thus, it can be concluded that Macromedia Flash 8-based teaching materials with STEAM approach to integrated thematic learning in elementary schools are practical and capable of improving student learning outcomes.